1999
DOI: 10.1148/radiology.210.2.r99fe37393
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Benign and Malignant Endometrial Disease: Hysterosonographic-Pathologic Correlation

Abstract: A thin endometrium or diffuse smooth endometrial thickening is predictive of benign endometrial histologic findings, but all women with endoluminal masses require further histologic evaluation to exclude malignant disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 10 publications
0
19
0
4
Order By: Relevance
“…Goldstein e Schwartz 21 , em 109 HSNG, tiveram 10 casos de espessamento endometrial, sendo apenas cinco hiperplasias (acerto de 50%). Laughead e Stones 22 , em 114 HSNG, tiveram 19 casos de espessamento endometrial, sendo apenas quatro hiperplasias (acerto de 21%), e Dubinsky et al 23 , em 88 HSNG, tiveram 30 casos de espessamento endometrial, com nenhum caso de hiperplasia.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Goldstein e Schwartz 21 , em 109 HSNG, tiveram 10 casos de espessamento endometrial, sendo apenas cinco hiperplasias (acerto de 50%). Laughead e Stones 22 , em 114 HSNG, tiveram 19 casos de espessamento endometrial, sendo apenas quatro hiperplasias (acerto de 21%), e Dubinsky et al 23 , em 88 HSNG, tiveram 30 casos de espessamento endometrial, com nenhum caso de hiperplasia.…”
Section: Discussionunclassified
“…Dubinsky et al 23 em 88 pacientes tiveram nove casos de câncer, e a HSNG teve sensibilidade de 89%, especificidade de 46%, VPP de 16% e VPN de 97%.…”
Section: Discussionunclassified
“…Endometrial polyps were ruled out by an office hysteroscopic procedure in women with thickened endometrium. Premenopausal women without any symptoms underwent imaging at least twice, and persistence of an early-proliferative-phase endometrium thicker than 12 mm was an indication for office hysteroscopy and endometrial sampling (6). The final outcome was categorized as resolution, persistence, or progression based on the findings either at hysterectomy or in the two final, consecutive endometrial samples.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, also Doppler studies of the endometrial vasculature have not been found helpful for this purpose, since no significant differences have been demonstrated between resistance and pulsatility indices in benign vs malignant causes of endometrial thickening [35,36]. Sonohysterography provides exquisite demonstration of the endometrial cavity and is able to describe accurately the morphological characteristics of endometrial lesions; however, it cannot provide differentiation between benign lesions and malignancies with absolute certainty, and all women with endoluminal masses still require histological evaluation to verify the presence of malignant disease [5,37,38,39,40].…”
Section: Abnormal Bleedingmentioning
confidence: 99%